Tecnologia assistiva e inclusão educacional de alunos com deficiência visual no ensino superior: a atuação do Núcleo de Acessibilidade da UFMA - TEIXEIRA , Andreia Fonsêca (2018)
Considering that the use of Assistive Technology (TA) extends the possibilities of learning of students with visual impairment, becoming important for the educational inclusion of these students, the present study aimed to investigate how the Accessibility Center of UFMA (NUACE -UFMA) operates the use of Assistive Technology in relation to the inclusion of people with visual impairment. This exploratory and descriptive research was quantitative and qualitative. The data were generated from the application of questionnaires to students with visual deficiency attended at NUACE-UFMA, conducting interviews with the professionals of the Center directly involved in the care of these students and observation of this place. The data generated by the closed questions of the questionnaires were treated by means of basic statistics, using the Microsoft Office Excel computer program, the data generated from the application of interviews and answers given to the open questions of the questionnaires were treated with the use of the analysis of the content. The results revealed that the Accessibility Center of the Federal University of Maranhão has been developing crucial actions for the educational inclusion of students with disabilities. A great effort was made by the Accessibility Center to meet the specific educational needs of students with visual impairment, including the availability of Assistive Technology resources and services for this audience. However, some factors make it difficult for NUACE to better serve these students, such as the lack of Assistive Technology equipment, inadequate physical space and insufficient specialized staff. From the Institutional Development Plan 2017-2021, it is perceived that UFMA recognizes these obstacles and intends to solve them, including through the acquisition of TA resources for visually impaired students. Nevertheless, the results allowed to conclude that the UFMA Accessibility Center, through the provision of Assistive Technology resources and services and other support services are fundamental for the promotion of the educational inclusion of the visually impaired student in higher education.